The Efforts of Indonesian Government In Increasing Teacher Quality Based On PISA Result In 2022: A Literature Review - Solihin, Riza Ramadhani; Susanto, Teguh Trianung Djoko; Fauziyah, Eka Puji; Yanti, Nur Vita Irma; Ramadhania, Andita Putri (Perspektif Ilmu Pendidikan, 2024)
The result of PISA for Indonesia in 2022 in literacy field, placed in 59 from 81 countries with the score 359, in numeration field, placed in 67 from 81 countries with the score 366, and for science field took placed in 65 with the score 383. Thus result are increasing, however is not good enough. Therefore, this research trying to depict the government efforts to increasing teacher quality in line with education as the implementation of national goals which is enrich the life of a nation. The task of enrich the life of a nation is not only imposed on teachers, but also on stakeholders through policies that have an impact on education. The result of this paper, with literature review as the research methodology, revealed that the government programme through teacher sharing (guru berbagi), teacher learns (guru belajar), Internet quota in pandemics, and the school operational fund indirectly affect the teacher quality and the increasing of PISA SCORE.